2021
DOI: 10.1002/ddr.21899
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid reduces oxidative stress and neuronal apoptosis after experimental subarachnoid hemorrhage by regulating Nrf2/ HO ‐1 pathway

Abstract: Oxidative stress is an early major pathological feature after subarachnoid hemorrhage (SAH) and involves in the development of acute brain injury, neuronal apoptosis and cerebral vasospasm following SAH. Antioxidant stress is an effective way to improve the prognosis of SAH. Oleanolic acid is a widely used triterpenoid from plants, which has strong antioxidant activities, hepatoprotective, anti‐inflammatory and anti‐cancer activities. However, whether oleanolic acid exerts its anti‐oxidant effect after SAH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…After Nrf2 agonist activity and toxicity screening, pesticides and drugs were removed manually, and 169 compounds were selected as potential Nrf2 agonists. Literature review results showed that 32 out of the 169 compounds in the list had clear evidence of Nrf2 agonistic activity and were mainly focused on compounds with high predictive indices (>0.85), demonstrating the accuracy of the predictive model (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…After Nrf2 agonist activity and toxicity screening, pesticides and drugs were removed manually, and 169 compounds were selected as potential Nrf2 agonists. Literature review results showed that 32 out of the 169 compounds in the list had clear evidence of Nrf2 agonistic activity and were mainly focused on compounds with high predictive indices (>0.85), demonstrating the accuracy of the predictive model (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…OA treatment induced apoptosis in osteosarcoma cells, a process regulated by Bcl-2 and caspase-3 through inhibition of the Notch signaling pathway [ 46 ]. In contrast, OA had protective effects in neuronal cells, ameliorating oxidative stress and neuronal apoptosis by inhibiting the Nrf2/HO-1 pathway [ 47 ]. These studies suggest that OA has protective effects on normal cells and anti-tumor effects on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found oleanolic acid to have good antioxidant effects in many diseases. In common brain tissue injury, oleanolic acid can activate the expression of antioxidant stress enzymes through the Nrf2/HOMX1 pathway, thereby down-regulating ROS in injured brain tissue in subarachnoid hemorrhage and achieving the function of protecting brain tissue [ 7 ]. In diabetes, oleanolic acid can reduce cellular oxygen stress through agonism of the Akt and MAPK pathways, thereby inhibiting the effects of insulin resistance during diabetes treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%